2015
DOI: 10.5194/npg-22-645-2015
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the validity of the ensemble Kalman filter without the intrinsic need for inflation

Abstract: Abstract. The ensemble Kalman filter (EnKF) is a powerful data assimilation method meant for high-dimensional nonlinear systems. But its implementation requires somewhat ad hoc procedures such as localization and inflation. The recently developed finite-size ensemble Kalman filter (EnKF-N) does not require multiplicative inflation meant to counteract sampling errors. Aside from the practical interest in avoiding the tuning of inflation in perfect model data assimilation experiments, it also offers theoretical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 49 publications
2
76
0
Order By: Relevance
“…The dynamical upwelling of model error differs from the sampling errors induced by nonlinear dynamics in perfect models, 25 treated in the modified EKF-AUS-NL (Palatella and Trevisan, 2015) and in the finite size ensemble Kalman filter, (EnKF-N) (Bocquet, 2011;Bocquet et al, 2015). Rather, we have shown that the upwelling of the unfiltered error through the Lyapunov filtration acts as a linear effect and is acute in the presence of additive model errors which are excited by transient instabilities.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The dynamical upwelling of model error differs from the sampling errors induced by nonlinear dynamics in perfect models, 25 treated in the modified EKF-AUS-NL (Palatella and Trevisan, 2015) and in the finite size ensemble Kalman filter, (EnKF-N) (Bocquet, 2011;Bocquet et al, 2015). Rather, we have shown that the upwelling of the unfiltered error through the Lyapunov filtration acts as a linear effect and is acute in the presence of additive model errors which are excited by transient instabilities.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the linear form of EKF-AUS does not include the upwelling of unfiltered error in its estimated covariance -inclusion of multiplicative inflation to the estimated error covariance compensates for the upwelling of unfiltered errors which is not represented in the recursion for EKF-AUS, and simulates the terms (34b), (34c) and (34d) in the KF-AUSE recursion. Multiplicative inflation may also be used to account for mis-estimation of forecast errors resultant from nonlinear evolution, but this mis-estimation may also be accounted for 20 using less ad hoc approaches including parameterizing this error with hyperpriors (Bocquet et al, 2015). We argue that the hyperprior in EnKF-N can, in principle, also be selected to take into account the structure of the ideal posterior for the reduced rank estimator, in the presence of model error, described by KF-AUSE (see also the discussion at the end of section 4.2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…, 1, 20). Sampling errors are systematically accounted for using the IEnKS finite-size version 5 (Bocquet, 2011;Bocquet and Sakov, 2012;Bocquet et al, 2015) which avoids the need for inflation and its costly tuning.…”
mentioning
confidence: 99%